Analysis Of Dog Bites in Kashmir: An Unprovoked Threat to Population - Kouser Sideeq Lone; Sufoora Bilquees; S Mohammad Salim Khan; Inaam Ul Haq (Medsci Publications, 2014)
Objectives: The study focuses on the analysis of regional distribution, pattern and outcome of dog bite injuries sustained in Kashmiri population and assessing the burden on society. Methods: In this retrospective survey antirabies clinic record of all patients who sought medical attention after a dog bite in tertiary centre of Kashmir SMHS hospital between April2010 to May 2013 were reviewed. Results: A total of 13852 patients registered over a period of three year with mean age 27.699±17.825. Majority cases were from Srinagar district with maximum frequency during summer season. The maximum victims (96%) were by stray dogs. About 96% of the patients had injuries to single body region and the lower limbs were affected in (46.5%). The majority of the patients who came to centre were of class III (74%) as most of the cases were referrals to tertiary centre. Inpatient treatment was required in (9%) patients. The ARC of SMHS has registered 8 deaths due to rabies in three year period with alarming increase of dog terror in Kashmiri population. Conclusions: Dog bites injuries in Kashmir are very frequent and dog population is increasing in alarming rates. Children who are younger than 10 years represent the high-risk group for dog attacks leading to alarming increase in anxiety disorders among children and directly or indirectly it inﬂuences the quality of life of Kashmir population. Therefore, prevention strategies should focus on public education and strict dog population control.